2003
DOI: 10.1063/1.1563601
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermodiffusion of polymers and colloids in solvent mixtures

Abstract: Results on thermodiffusion of poly͑ethylene oxide͒ and colloidal boehmite (␥-AlOOH͒ rods in ethanol/water mixtures are presented. Data were obtained using thermal diffusion forced Rayleigh scattering. The sign of the Soret coefficient of the boehmite rods changes from positive to negative with increasing water content, i.e., at sufficiently high water content the colloidal particles move to higher temperatures. The sign of the Soret coefficient of the poly͑ethylene oxide͒ in ethanol/water mixtures is negative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 25 publications
(15 reference statements)
10
68
0
Order By: Relevance
“…[16][17][18][19] Some aqueous solutions of polymers show negative Soret coefficients, which correspond to a migration of the polymers to the warm side. [20][21][22][23][24][25] It has been revealed that a sign of S T of the polymer in solution can occur as function of the solution temperature as well as of the solvent composition. [26][27][28][29][30] For liquid mixtures composed of small molecules thermally induced sign change of S T have been studied by several researchers [31][32][33][34] , sometime those sign changes could be correlated with structural changes in the liquid mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Some aqueous solutions of polymers show negative Soret coefficients, which correspond to a migration of the polymers to the warm side. [20][21][22][23][24][25] It has been revealed that a sign of S T of the polymer in solution can occur as function of the solution temperature as well as of the solvent composition. [26][27][28][29][30] For liquid mixtures composed of small molecules thermally induced sign change of S T have been studied by several researchers [31][32][33][34] , sometime those sign changes could be correlated with structural changes in the liquid mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The Soret coefficient S T of poly(ethylene oxide) [PEO] in the solvent mixture ethanol/water increases with temperature, whereas the slope is positive and decreases with increasing water content. 21,22,26,27 The Soret coefficient S T changes sign from negative to positive with increasing temperature for ethanol/water mixtures with a high ethanol content, while S T is always positive for PEO in pure water. A similar temperature dependence of S T has been observed for dextran in water.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer moves to the cold side in high water compositions (S T > 0), while it migrates to hot side in low water compositions (S T < 0). 31,36,37 The sign of S T was also changed by varying the temperature in a certain composition range of solvent mixture, although in pure water the S T of PEO was positive. A calculation of lattice chamber model for this system showed that hydrogen bonding plays a key role in describing the sign change behavior of the polymer.…”
mentioning
confidence: 99%
“…Generally, it was applied to different kind of mixtures: simple fluid mixtures [36,113,75,111,183,185] polymer solutions [34,72,123], micellar solutions [109,110] and colloidal dispersions [33,106]. The advantages of the method are a small temperature difference (∼20 µK) and a small fringe spacing (∼20 µm) which keeps the system close to the thermal equilibrium and allows also the investigation of slow diffusing systems such as polymers and colloids.…”
Section: Thermal Diffusion Forced Rayleigh Scatteringmentioning
confidence: 99%
“…Each state i has an energy E i . The canonical partition function is given by 33) where the "inverse temperature" β is defined as (k B T ) −1 . The probability that the system occupies a microstate i is given by…”
Section: Two-chamber Lattice Modelmentioning
confidence: 99%